2022
DOI: 10.3389/fpubh.2022.909125
|View full text |Cite
|
Sign up to set email alerts
|

Crocetin Protected Human Hepatocyte LO2 Cell From TGF-β-Induced Oxygen Stress and Apoptosis but Promoted Proliferation and Autophagy via AMPK/m-TOR Pathway

Abstract: ObjectiveTo investigate the protective effects of crocetin against transforming growth factor-β (TGF-β)—induced injury in LO2 cells.MethodsHuman hepatocyte LO2 cells were pre-treated with crocetin (10 μM) for 6, 12, and 24 h, and then induced by TGF-β. Proliferation, oxidative stress, apoptosis, autophagy, and related proteins were assessed.ResultsCrocetin pre-treating promoted proliferation but suppressed apoptosis in TGF-β-induced LO2 cells. Crocetin protected LO2 cells from TGF-β-induced inflammation and ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Crocin, by modulating the MAPK signaling pathway and reducing TNF-α levels, exhibits anti-inflammatory and anti-apoptotic activity [35]. Furthermore, Crocetin, through promoting cell proliferation and autophagy and regulating the AMPK signaling pathway, inhibits cell apoptosis and inflammation, thereby protecting cells from damage [36]. These research results are consistent with our experimental results, further illustrating that WG may achieve efficacy in treating jaundice and hepatitis through its anti-inflammatory effects.…”
Section: In Vitro Validationsupporting
confidence: 87%
“…Crocin, by modulating the MAPK signaling pathway and reducing TNF-α levels, exhibits anti-inflammatory and anti-apoptotic activity [35]. Furthermore, Crocetin, through promoting cell proliferation and autophagy and regulating the AMPK signaling pathway, inhibits cell apoptosis and inflammation, thereby protecting cells from damage [36]. These research results are consistent with our experimental results, further illustrating that WG may achieve efficacy in treating jaundice and hepatitis through its anti-inflammatory effects.…”
Section: In Vitro Validationsupporting
confidence: 87%
“…NR0B1 has been reported to transcriptionally repress the expression of GSK3β in cervical cancer, 28 and inhibition of GSK3β activity activates the adenosine monophosphate‐activated protein kinase (AMPK)/mammalian target of rapamycin (mTOR) signaling pathway, 29 resulting in the activation of autophagic molecules. 30 , 31 In this case, we speculated that NR0B1 may regulate autophagy through controlling the GSK3β‐targeted molecules in HCC cells. Then, we confirmed that NR0B1 OE clearly decreased GSK3β expression in the levels of mRNA and protein (Figure 6A,B ), whereas NR0B1 KD increased its expression (Figure 6C ).…”
Section: Resultsmentioning
confidence: 97%
“…CCT has been shown to have both antioxidant and anti-inflammatory properties [ 15 , 21 , 53 , 54 ]. It has been shown that CCT is capable of lowering the levels of oxidative stress biomarkers such as malondialdehyde (MDA) [ 55 , 56 ]. In fact, a recent publication has shown that CCT (from saffron) at the same concentration as the one we used (10 μM) is the most effective dose for reducing MDA levels [ 56 ].…”
Section: Discussionmentioning
confidence: 99%